Pengaruh Motivasi Belajar, Lingkungan Belajar dan Kompetensi Pedagogik Guru Terhadap Prestasi Belajar Siswa Mata Pelajaran Ekonomi SMA Negeri 1 Lumbang Kabupaten Probolinggo - Ahmad Hasan Nidhomuddin; Sugeng Pradikto (Journal of Creative Student Research, 2025)
Knowing how learning motivation and the learning environment influence student learning achievement in economics classes at SMA Negeri 1 Lumbang, Probolinggo Regency is the aim of this research. This research used a proportional random sampling strategy, a quantitative correlational descriptive causality approach, and a sample size of 58 respondents. Questionnaires or Google Forms as well as recording and observing report cards are the methods used to collect data. Multiple linear regression analysis is the method used. The research findings mostly show that the desire to learn and learning achievement are influenced positively and significantly by the two independent variables (t value 2.846 > t table 2.00404, significant value t = 0.006 < 0.05). Apart from that, there is a fairly large relationship between learning achievement and the learning environment (t value 3.031 > t table 2.00404, significant value t = 0.004 < 0.05). Learning achievement is significantly influenced by these two independent factors at once (calculated F value 56.133 > 3.16 with a significance value of 0.000 < 0.05). Furthermore, the coefficient of determination test for the R square value was 0.671 or 67.1%, which shows that these two factors influence learning achievement, while the remaining 32.9% is influenced by other factors.